If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(x + 1) = 20 Reorder the terms: 11(1 + x) = 20 (1 * 11 + x * 11) = 20 (11 + 11x) = 20 Solving 11 + 11x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 11x = 20 + -11 Combine like terms: 11 + -11 = 0 0 + 11x = 20 + -11 11x = 20 + -11 Combine like terms: 20 + -11 = 9 11x = 9 Divide each side by '11'. x = 0.8181818182 Simplifying x = 0.8181818182
| Y=4x/5 | | 48/u=12 | | -10x-5+7x=45 | | 7x+8=5x-6 | | 34(21-6.5x)=16(6x-8)+49.5 | | 2a+5=a-2 | | 1/5-9×/5=3x-7 | | 9n=4-35 | | ln(x)=-1.71636 | | -7v+3(v-5)=-39 | | 8x^2=16x-40/9;x1/3 | | 1-9x/5=3x-7 | | 2=-2(y+3) | | 15x+15y-2xy=0 | | 50+2x= | | -5(2x-19)=2(x-8)-9 | | 2(c+2)+6=5(x-5) | | 125x+1382=284 | | 3(z-4)-1=4(z-5) | | x*ln(x)-2=0 | | 2x^2+30x+99=0 | | y^2-2y-104=0 | | 4x^2-23x-35=o | | 12x+13=21 | | 8(x-2)=-6(x+4)+43 | | u+7=-6 | | (-5a^6-7)-(-14a^6)= | | x=100+-3x | | Y^3-7y^2=8 | | 32+4x=4(-x+7)-44 | | -2+v=3 | | 9x-88=2x-11 |